Current opportunities and challenges for scientists in the field of sports biomechanics - Gui Yulong, (Theory and Practice of Physical Culture, 2024)
Objective of the study was to provide the academic community with a brief overview of the current state and development of sports biomechanics. Methods and structure of the study. General research methods are used, such as analysis and synthesis, formalization, deduction, generalization, as well as the historical method. Scopus, Web of Science, Science Direct and Elibrary databases were used for the literature review. We considered publications in which biomechanics appears both from a general theoretical position and from the point of view of its specific applications. Results and conclusions. As a scientific field, sports biomechanics conducts an in-depth analysis of the characteristics and patterns of biomechanical movement of organisms. This is a key aspect for understanding the complex mechanisms of movement in biological systems and for effectively controlling human movements. In this context, the biomechanics of sports promises to achieve even deeper development and provide more advanced theoretical and technical support for human health and physical activity.